The technical level of small-town shoemaking in Gdańsk Pomerania in the 14th century - Blusiewicz, Karolina (Archaeologia Historica Polona, 2021)
Based on the late medieval leather artefacts from Puck, Gniew, Lębork and Chojnice, an attempt was made to assess the level of shoemaking production at that time. Microscopic analyses of leather goods and production waste proved that in the field of tanning the activities related to the mechanical treatment of leather were carefully performed, although with insufficient professional knowledge concerning the process. The results of the identification of the animal origin of the leather confirmed the purposeful selection of raw material with different properties for individual footwear elements and the ability to properly cut it. The quality of the shoemaking products was highly rated in terms of technology and style. However, in the analysed collections a clearly perceptible difference in craftsmanship and assortment of products from Gniew and the other three towns was noticed.